Trends and patterns of antimicrobial consumption at Benjamin Mkapa Zonal Referral Hospital, Dodoma, Tanzania: a cross-sectional retrospective analysis - Moshi Moshi Shabani; Kauke Bakari Zimbwe; Yusto Julius Yona; Charity Alphonce Chiwambo; Alphonce Bilola Chandika; Humphrey Sawira Kiwelu (BMJ Open)
Objective This study assessed the trends and patterns of antimicrobial consumption (AMC) from 2020 to 2021, 2021–2022 and 2022–2023 at the Benjamin Mkapa Zonal Referral Hospital (BMH) in Dodoma, Tanzania.Design A retrospective cross-sectional study was conducted to collect AMC data for three financial years with respective denominators. The data were computed using the AMC Tool 2019 v1.9.0 and defined daily dose per 1000 inhabitants per day (DID).Setting The BMH, Dodoma, Tanzania.Participants This study surveyed quantities of antimicrobials procured at the BMH. It did not have any human participants.Outcome measures AMC was quantified in DID. The comparisons were made based on the DID of all surveyed antimicrobials, taking into account oral and parenteral administration and based on pharmacological classes. Further, DIDs were presented based on the 2023 WHO Access (A), Watch (W) and Reserve (R) (AWaRe) classification.Results In 29 assessed antimicrobials, the DIDs for 2020–2021, 2021–2022 and 2022–2023 were 3.0852, 3.5892 and 3.9213, respectively. The average DID per year was 3.5319, with a mean of 2.4207±1.9765 DID per year. The topmost consumed antimicrobials over the 3 years (doxycycline, azithromycin, amoxicillin/beta-lactamase inhibitors, ampicillin/cloxacillin, amoxicillin/flucloxacillin, ceftriaxone, nitrofurantoin and clarithromycin) account over 90% of consumption. The most highly consumed therapeutic classes were beta-lactam antibacterial penicillins (34.71%), macrolides, lincosamides, streptogramins and others (25.75%), followed by tetracycline (23.88%). The AWaRe categorisation and antimicrobials not recommended (ANR) distribution were as follows: Access-51.61%, Watch-31.96%, Reserve-0.00%, and ANR-16.43%, respectively.Conclusion For every 1000 patients attending the BMH per day, our study found 2.4207±1.9765 DIDs of an antimicrobial were consumed. The most consumed antimicrobials include doxycycline, azithromycin, amoxicillin/beta-lactamase inhibitor, ceftriaxone and metronidazole. To combat antimicrobial resistance effectively, it is imperative to institute a hospital policy for antimicrobial stewardship that prioritises the utilisation of a hospital formulary and antibiograms for the procurement of antimicrobials at the BMH.